A photothermal-flame-retardant synergistic composite aerogel and a preparation method and application thereof

CN122479725BActive Publication Date: 2026-10-20GUANGXI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610925441.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-20
Estimated Expiration
2046-06-25

AI Technical Summary

Technical Problem

[0006]鉴于上述内容,有必要提供一种光热-阻燃协同的复合气凝胶及其制备方法与应用,其解决了现有吸油材料高粘原油吸附慢、易燃、易坍塌的技术难题,可用于海上溢油处理和含油废水净化

Benefits of technology

[0021]与现有技术相比,本发明至少具有如下有益效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122479725B_ABST
    Figure CN122479725B_ABST
Patent Text Reader

Abstract

The application discloses a kind of photothermal-flame-retardant synergistic composite aerogel and its preparation method and application, belong to functional material technical field.The composite aerogel includes bacterial cellulose three-dimensional skeleton, loaded on its titanium nitride nanoparticles, and the three-dimensional network formed by γ-glycidyl ether oxygen propyl trimethoxysilane and polyethylene imine covalent crosslinking, with multi-level pore structure, at 80% compression strain, cycle compression 20 times without collapse.Under simulated sunlight irradiation, titanium nitride converts light energy into heat energy, makes aerogel surface rapidly warm, in situ reduces crude oil viscosity, realizes rapid adsorption, and the adsorption capacity retention rate is >95% after 10 times oil absorption-extrusion cycle.The limiting oxygen index of the aerogel is 24%, with flame-retardant performance.In thermogravimetric analysis, the carbon residue rate of bacterial cellulose aerogel at 800 DEG C is only about 17%, and the composite aerogel is increased to 35%.Vertical combustion test is carried out, reaches V-0 level, and the flame-retardant performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials technology, specifically relating to a photothermal-flame synergistic composite aerogel, its preparation method, and its application. Background Technology

[0002] With the continuous expansion of global marine oil transportation and offshore crude oil extraction, oil spills are becoming increasingly frequent. Coupled with the uncontrolled discharge of oily wastewater from industry, these incidents pose irreversible and serious threats to marine ecosystems, aquatic environments, and human health. Aerogel materials, due to their unique advantages such as low density, high porosity, and high specific surface area, have become a highly sought-after porous functional material in the fields of oil-water separation and crude oil adsorption.

[0003] Currently, common materials used for crude oil adsorption include traditional oil-absorbing aerogels, polyurethane sponges, and pure cellulose aerogels. However, these materials face three long-standing technical bottlenecks in actual crude oil processing. First, high-viscosity crude oil is difficult to adsorb: Crude oil has extremely poor fluidity at room temperature and even low temperatures at sea surface, making it impossible to quickly absorb it using capillary force alone, resulting in a slow adsorption rate and a significant decrease in actual adsorption capacity. Second, there are significant fire safety hazards: Polymer-based or cellulose-based materials are inherently flammable, and coupled with the high flammability of crude oil, once saturated, exposure to open flames or static electricity can easily trigger secondary fires or even explosions. Third, mechanical structural stability is poor: After adsorption saturation, physical extrusion is required for recycling and reuse. However, traditional aerogels are prone to irreversible collapse of their internal framework after repeated high-strain extrusions, resulting in short cycle life and poor economic efficiency.

[0004] To address these issues, existing research attempts to improve oil absorption rates by adding photothermal fillers (such as graphene and MXene) or by introducing flame retardants to enhance fire resistance. However, different functional improvements often hinder each other and are difficult to integrate within the same material system. While carbon-based photothermal fillers have high photothermal conversion efficiency, they are inherently flammable and their introduction often disrupts the original three-dimensional network of the aerogel, leading to a significant decrease in mechanical strength and flame retardant properties. On the other hand, while phosphorus- or nitrogen-based flame retardants can improve fire safety, they easily clog pores, thus reducing the adsorption capacity and selectivity for crude oil. In other words, current technologies have consistently failed to combine the three properties of "rapid viscosity reduction and oil absorption," "high flame retardancy," and "resistance to compression cycles" into a single product.

[0005] Therefore, the industry urgently needs to develop a multifunctional composite aerogel material that can break through the aforementioned performance barriers and simultaneously achieve photothermal viscosity reduction, rapid oil absorption, high flame retardancy and fire prevention, strong mechanical compression resistance, and recyclability. Summary of the Invention

[0006] In view of the above, it is necessary to provide a photothermal-flame synergistic composite aerogel, its preparation method and application, which solves the technical problems of slow adsorption of high-viscosity crude oil, flammability and easy collapse of existing oil-absorbing materials, and can be used for marine oil spill treatment and oily wastewater purification.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] A composite aerogel comprising: a bacterial cellulose three-dimensional framework; titanium nitride nanoparticles loaded on the bacterial cellulose three-dimensional framework; and a covalently cross-linked network formed on the bacterial cellulose three-dimensional framework by γ-glycidoxypropyltrimethoxysilane and polyethyleneimine through an epoxy ring-opening reaction and a silanol condensation reaction.

[0009] Furthermore, in this invention, the composite aerogel has a multi-level porous structure comprising macropores, micropores, and mesopores, and the titanium nitride nanoparticles are uniformly distributed on the surface and pore walls of the bacterial cellulose three-dimensional framework with minimal aggregation.

[0010] In this invention, the surface of the composite aerogel is further modified with a hydrophobic modifier, and its water contact angle is >150°; the hydrophobic modifier comprises trichlorooctadecylsilane.

[0011] Furthermore, in this invention, the covalent cross-linked network ensures that after the composite aerogel undergoes more than 20 cycles of compression at 80% compressive strain, its stress-strain curve essentially coincides with that of the first compression, and there is no irreversible structural collapse.

[0012] Furthermore, in this invention, the composite aerogel has a limiting oxygen index of 24% and achieves a V-0 rating through the UL-94 vertical burning test.

[0013] The present invention also proposes a method for preparing the above-described composite aerogel, comprising the following steps.

[0014] (1) The bacterial cellulose dispersion was mixed with titanium nitride nanoparticles and ultrasonically dispersed to obtain a mixed dispersion.

[0015] (2) Add γ-glycidoxypropyltrimethoxysilane and polyethyleneimine aqueous solution to the mixed dispersion in sequence, stir and react to obtain crosslinking reaction solution.

[0016] (3) After pre-freezing the cross-linking reaction solution, freeze-dry it to obtain composite aerogel.

[0017] In this invention, after adding γ-glycidyl etheroxypropyltrimethoxysilane, the mixture is stirred for 0.5 to 2 hours, and after adding an aqueous solution of polyethyleneimine, the mixture is stirred for 1 to 4 hours. In step (3), the pre-freezing temperature is -60°C to -80°C, and the time is 1 to 3 hours.

[0018] Furthermore, this invention also includes a hydrophobic modification step: the composite aerogel obtained in step (3) is immersed in an organic solvent solution containing trichlorooctadecylsilane, and then dried in a vacuum oven at 60~80℃ for 0.5~2 hours to obtain a hydrophobic modified composite aerogel.

[0019] The present invention also proposes an application of the composite aerogel as described above in photothermal assisted adsorption of crude oil. Under light irradiation, the titanium nitride nanoparticles in the composite aerogel convert light energy into heat energy to reduce the viscosity of crude oil, and selectively adsorb crude oil based on the superhydrophobicity of the composite aerogel.

[0020] Furthermore, in this invention, the composite aerogel is used for marine oil spill treatment or oily wastewater purification.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects.

[0022] 1. Under one day of sunlight, the BTPG composite aerogel of this invention adsorbs crude oil droplets in only 7 seconds, with a saturated adsorption capacity as high as 21.49 g / g, which is 179% higher than the control sample without GPTMS (7.68 g / g) and 122% higher than the control sample without PEI (9.69 g / g). The photothermal conversion effect of TiN nanoparticles raises the surface temperature of the aerogel to about 80°C within 60 seconds, effectively reducing the viscosity of crude oil. At the same time, the covalent cross-linked network and hierarchical porous structure constructed by GPTMS / PEI provide sufficient oil storage space and rapid transport channels. The three factors work synergistically to achieve rapid adsorption and high-capacity capture of high-viscosity crude oil.

[0023] 2. In the UL-94 vertical burning test, the BTPG composite aerogel of this invention achieved the highest rating of V-0, extinguishing immediately upon removal of the flame without melting or dripping; the limiting oxygen index reached 24.0%, an improvement of 28.3% compared to pure BC aerogel (18.7%); the char residue at 800℃ was as high as 35%, significantly better than pure BC (17%) and the cross-linked matrix without TiN (22%). During combustion, TiN induces rapid char formation of the bacterial cellulose skeleton and acts as a rigid supporting skeleton embedded in the char layer, forming a dense physical barrier layer that effectively inhibits heat transfer and the release of combustible gases. The supporting effect of TiN on the char layer at high temperatures allows the material to achieve high flame retardancy while avoiding the mechanical property degradation problems caused by traditional flame retardants.

[0024] 3. After 20 cycles of compression at 80% high compressive strain, the stress-strain curve of the BTPG composite aerogel of this invention largely coincides with that of the first compression, with no significant attenuation of the peak stress. After unloading, the sample essentially returns to its original state without irreversible structural collapse. After 10 oil absorption-extrusion cycles, the adsorption capacity retention rate still exceeds 95%. This is because the covalent cross-linked network formed by GPTMS and PEI on the bacterial cellulose skeleton significantly enhances the strength of the three-dimensional skeleton, giving the material excellent elastic recovery and fatigue resistance. This effectively overcomes the defects of traditional aerogels, such as easy skeleton collapse and short service life after repeated extrusion, and has good application economy. Attached Figure Description

[0025] Figure 1 The Fourier transform infrared (FT-IR) spectrum of the BTPG composite aerogel prepared in Example 1 of this invention is shown.

[0026] Figure 2 The X-ray diffraction (XRD) pattern of the BTPG composite aerogel prepared in Example 1 of this invention is shown, with the TiN standard card (PDF#01-071-9845) also labeled.

[0027] Figure 3 The images shown are scanning electron microscope (SEM) images of the BTPG composite aerogel prepared in Example 1 of this invention; wherein, (a) is the SEM image of pure BC aerogel, (b) is the SEM image of pure TiN nanoparticles, (c) is the SEM image of BTPG composite aerogel at low magnification, and (d) is the SEM image of BTPG composite aerogel at high magnification.

[0028] Figure 4 The mechanical compression performance test graphs of the BTPG composite aerogel prepared in Example 1 of the present invention are shown. Among them, (a) is the compression stress-strain curve of BTPG, BTG, BTP and BC at 80% strain, (b) is the stress-strain curve of BTPG after the first compression and after 1, 15 and 20 cycles of compression at 80% strain, and (c) is a bar chart comparing the maximum compressive stress and elastic modulus of the four groups of samples of BTPG, BTG, BTP and BC.

[0029] Figure 5 The figures show a comparison of the hydrophobic properties of the BTPG composite aerogel prepared in Example 1 of this invention and the pure BC aerogel; where (a) is a water contact angle test photo of BTPG and (b) is a water contact angle test photo of pure BC.

[0030] Figure 6The image shows the photothermal performance test results of the BTPG composite aerogel prepared in Example 1 of this invention; where (a) is the photothermal heating-cooling curve of the three groups of samples, BTPG, BTG and BTP, under 1 solar intensity (lamp on / off cycle), and (b) is the heating-cooling curve of BTPG under different solar intensities (1, 1.5 and 2 solar intensities).

[0031] Figure 7 The image shows the oil absorption performance test of the BTPG composite aerogel prepared in Example 1 of this invention; where (a) is a comparison photo of the adsorption time of crude oil droplets on the BTPG surface under light conditions (1 sun) and no light conditions, and (b) is a photo of the adsorption effect of BTPG under light (20 s) in an actual oil-water separation scenario.

[0032] Figure 8 The graphs show the crude oil adsorption capacity and cycle stability of the BTPG composite aerogel prepared in Example 1 of this invention and the control sample; where (a) is a bar chart comparing the saturated adsorption capacity of BTPG, BTG and BTP on crude oil, and (b) is the adsorption capacity retention curve of BTPG in 10 oil absorption-squeeze cycles.

[0033] Figure 9 Thermogravimetric analysis (TGA) curves of the BTPG composite aerogel prepared in Example 1 of the present invention and the control sample are shown; where (a) is the thermogravimetric (TG) curve (the vertical axis is the mass percentage) and (b) is the derivative thermogravimetric (DTG) curve (the vertical axis is the mass change rate).

[0034] Figure 10 The bar chart shows the limiting oxygen index (LOI) test results of the BTPG composite aerogel prepared in Example 1 of this invention and the control sample.

[0035] Figure 11 The images show the UL-94 vertical combustion test results of the BTPG composite aerogel prepared in Example 1 of this invention and the control sample; wherein, (a) is a combustion test image of pure BC aerogel, (b) is a combustion test image of BPG (crosslinked matrix without TiN), and (c) is a combustion test image of BTPG composite aerogel.

[0036] Figure 12 The diagram shows the verification of the oil absorption and flame retardant mechanism of the BTPG composite aerogel prepared in Example 1 of this invention; where (a) is the BET differential pore size distribution curve (linear coordinates), (b) is the BET differential pore size distribution curve (logarithmic coordinates), (c) is the photothermal heating curve of BTPG under different light intensities, and (d) is a comparison of the XRD patterns of BTPG before and after combustion. Detailed Implementation

[0037] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0038] The BC / TiN / GPTMS / PEI composite aerogel prepared in this invention will be referred to as "BTPG" in the following text. "BTPG" and "BTPG composite aerogel" have the same meaning and can be used interchangeably.

[0039] Example 1.

[0040] This embodiment proposes a BTPG composite aerogel, the preparation method of which is as follows.

[0041] (1) Raw material preparation: Weigh 0.095 g of nano titanium nitride (TiN, average particle size 20 nm), mix with 12.5 g of bacterial cellulose (BC) dispersion (solid content 0.80 wt%), and ultrasonically disperse for 10 min to obtain a uniform mixture.

[0042] (2) Crosslinking reaction: 0.2 g of γ-glycidoxypropyltrimethoxysilane (GPTMS) was pipetted into the above mixture and stirred at room temperature for 1 h; then 1 g of polyethyleneimine (PEI) aqueous solution (mass fraction 20wt%) was added and stirred for another 3 h to obtain the crosslinking reaction solution.

[0043] (3) Freeze-drying: Pour the above cross-linking reaction solution into a 25 mL beaker, seal it with a sealing film and poke several small holes with a needle, place it in a -80℃ freezer for 2 h, take it out and quickly transfer it to a freeze dryer, freeze-dry it at -55℃ and vacuum degree ≤10Pa for 48 h to obtain the BTPG composite aerogel matrix.

[0044] (4) Hydrophobic modification: Prepare hydrophobic modification solution: Add 0.5 mL of trichlorooctadecylsilane to 49.5 mL of n-hexane and stir magnetically for 10 min. Immerse the BTPG aerogel obtained in step (3) into the above modification solution, stir magnetically slowly for 15 min, let it stand for 1 h, take it out and dry it in a vacuum oven at 65℃ for 3 h to obtain hydrophobic modified BTPG composite aerogel (unless otherwise specified, the following performance tests all use the hydrophobic modified sample).

[0045] Tests showed that the BTPG composite aerogel prepared in this embodiment had a water contact angle of 150.2°, a limiting oxygen index of 24.0%, and achieved a V-0 rating in the UL-94 vertical combustion test. The saturated adsorption capacity for crude oil was 21.49 g / g, and it did not collapse irreversibly after 20 cycles of compression at 80% compressive strain.

[0046] Comparative Example 1: Preparation of pure BC aerogel.

[0047] 12.5 g of BC dispersion (solid content 0.80 wt%) was poured into a 25 mL beaker, sealed with a membrane and punched with holes, frozen at -80℃ for 2 h, and then freeze-dried for 48 h (under the same conditions as in Example 1) to obtain pure BC aerogel. After hydrophobic modification with trichlorooctadecylsilane according to step (4) of Example 1, it was used for performance testing.

[0048] Comparative Example 2: Preparation of BPG composite aerogel (without TiN).

[0049] Except for the absence of TiN, the remaining steps were exactly the same as in Example 1, resulting in BPG composite aerogel. After hydrophobic modification with trichlorooctadecylsilane according to step (4) of Example 1, it was used for performance testing.

[0050] Comparative Example 3: Preparation of BTG composite aerogel (without PEI).

[0051] Except for the absence of PEI aqueous solution, the remaining steps were exactly the same as in Example 1, resulting in BTG composite aerogel. After hydrophobic modification with trichlorooctadecylsilane according to step (4) of Example 1, it was used for performance testing.

[0052] Comparative Example 4: Preparation of BTP composite aerogel (without GPTMS).

[0053] Except for the absence of GPTMS, the remaining steps were exactly the same as in Example 1, resulting in BTP composite aerogel. After hydrophobic treatment with trichlorooctadecylsilane according to the hydrophobic modification method in step (4) of Example 1, it was used for performance testing.

[0054] Structural characterization and performance testing.

[0055] The following performance tests are all represented by the BTPG composite aerogel prepared in Example 1 and described in detail.

[0056] 1. Chemical structure characterization (FT-IR).

[0057] The BTPG composite aerogel prepared in Example 1 was analyzed using Fourier transform infrared spectroscopy, such as... Figure 1 As shown.

[0058] from Figure 1 It can be seen that the characteristic absorption peak of BC is located at 3348 cm⁻¹. -1 (OH stretching vibration), 2919 cm -1 (CH stretching vibration), 1095 cm -1 (COC pyranose ring skeletal vibration). The characteristic absorption peak of PEI is located at 1591 cm⁻¹. -1 (NH bending vibration). The characteristic epoxy group absorption peak of GPTMS is located at 909 cm⁻¹. -1 .

[0059] In the FT-IR spectrum of BTPG, GPTMS has a 909 cm⁻¹ -1 The complete disappearance of the epoxy peak indicates that the epoxy group underwent a ring-opening reaction; BC at 3348 cm⁻¹ -1 The hydroxyl peak intensity decreased significantly, indicating that the hydroxyl group participated in the condensation reaction; PEI's 1591 cm⁻¹ -1 The NH peak remains, albeit with a reduced intensity, indicating that PEI has successfully integrated into the network. Meanwhile, the CH and CO backbone peaks of BC remain stable. These results demonstrate that an epoxy ring-opening and hydroxyl condensation reaction occurred among BC, GPTMS, and PEI, forming a three-dimensional cross-linked network with BC as the backbone and the components connected by covalent bonds.

[0060] 2. Crystal structure characterization (XRD).

[0061] The BTPG composite aerogel prepared in Example 1 was analyzed using X-ray diffraction. Figure 2 As shown.

[0062] from Figure 2 As can be seen, the BTPG sample exhibited characteristic diffraction peaks that perfectly matched those on the TiN standard card (PDF#01-071-9845), corresponding to the (111), (200), (220), and (311) crystal planes of TiN, respectively. The sharp peak shapes indicate that the crystal structure of TiN remained intact during the composite process, maintaining good crystallinity. Simultaneously, the intensity of the cellulose type I characteristic peaks of BC (approximately 14.9°, 16.8°, and 22.7°) significantly decreased, and the peak shapes broadened, indicating that the crosslinking reaction weakened the hydrogen bond network of BC and reduced its crystallinity. These results demonstrate that TiN and the BC framework achieved effective composite formation, providing a stable structural basis for subsequent photothermal, flame-retardant, and mechanical properties.

[0063] 3. Microscopic morphology characterization (SEM).

[0064] The morphology of pure BC, pure TiN, and BTPG composite aerogels was observed using scanning electron microscopy, such as... Figure 3 As shown. Among them, Figure 3(a) is pure BC aerogel, showing a typical three-dimensional porous fiber network structure. The fibers intertwine to form large channels, providing a flexible framework for the composite aerogel. Figure 3 (b) is pure TiN nanoparticles, which are nano-sized particles with uniform particle size; Figure 3 (c) is a low-magnification SEM image of the BTPG composite aerogel, which still retains the three-dimensional interconnected porous network structure of BC, ensuring high porosity and material transport channels. Figure 3 (d) is a high-magnification SEM image of the BTPG composite aerogel, clearly showing that TiN nanoparticles are uniformly loaded and anchored on the BC fiber surface with minimal aggregation. This hierarchical structure provides the microstructural basis for the material's excellent photothermal adsorption, flame retardancy, and mechanical properties.

[0065] 4. Mechanical compression performance test.

[0066] The compressive properties of the BTPG composite aerogel prepared in Example 1 were tested using a universal testing machine. The sample was prepared as a cylinder with a diameter of approximately 30 mm and a height of approximately 10 mm. The test was conducted at a compression rate of 1 mm / min, with a maximum compressive strain of 80%. Multiple cyclic compression tests were performed. The maximum compressive stress and elastic modulus of the four groups of samples (BTPG, BTG, BTP, and BC) were compared. The results are as follows: Figure 4 As shown.

[0067] Figure 4 (a) shows the first compressive stress-strain curves of BTPG, BTP, BTG and BC at 80% strain. The curves show typical three-segment characteristics of elastic deformation, plateau region and densification region. The stress rises slowly in the plateau region, indicating that the material has excellent flexible deformation capability. Figure 4 (b) shows the stress-strain curves of BTPG after the first compression at 80% strain and after 1, 15 and 20 cycles of compression. It can be seen that the curves highly coincide with the first compression, the peak stress does not decrease significantly, and the sample basically returns to its original state after unloading, without irreversible plastic deformation or structural collapse. Figure 4 (c) is a bar chart comparing the maximum compressive stress and elastic modulus of the four sample groups: BTPG, BTG, BTP, and BC. The maximum compressive stress and elastic modulus of BTPG are significantly higher than those of BC, BTG, and BTP, indicating that the TiN and GPTMS / PEI crosslinking network synergistically enhance the mechanical properties of the material. These results demonstrate that the covalent crosslinking network constructed in this invention endows the aerogel with excellent elastic recovery properties and fatigue resistance, enabling it to withstand repeated high-strain extrusion without damage, thus providing mechanical protection for multiple oil absorption-extrusion cycles.

[0068] 5. Hydrophobicity test.

[0069] The water contact angle of the BTPG composite aerogel and pure BC aerogel prepared in Example 1 was tested using a contact angle meter. Five different locations were selected for each sample, and the average value was taken. The results are as follows: Figure 5 As shown.

[0070] Figure 5 (a) The water contact angle of BTPG is shown to be 150.2°. Figure 5 (b) The water contact angle of pure BC is 140.3°. BTPG has a water contact angle greater than 150°, meeting the superhydrophobic standard. This is because the hydrophobic modification with trichlorooctadecylsilane successfully introduced long-chain alkyl groups onto the aerogel surface, reducing surface energy. Simultaneously, the porous and rough structure of the material itself further enhances the hydrophobic effect. Superhydrophobicity ensures that BTPG is not wetted in the aqueous phase, allowing for selective adsorption of oily substances, providing a crucial guarantee for efficient oil-water separation and crude oil adsorption.

[0071] 6. Photothermal performance test.

[0072] The photothermal performance of the three groups of samples (BTPG, BTG, and BTP) prepared in Example 1 was tested using a simulated solar light source (AM 1.5G filter). The samples were placed on a heat-insulating stage, and the surface temperature was recorded in real time using an infrared thermal imager. The light intensity was set to 1, 1.5, and 2 solar constants (1 Sun = 1000 W / m²), respectively. 2 ), the result is as follows Figure 6 As shown.

[0073] Figure 6 (a) shows the heating-cooling curves of the three groups of samples under one solar radiation intensity. After the light source was turned on, all three groups of samples could rapidly heat up to about 80°C and reach thermal equilibrium within about 60 s; after the light source was turned off, the temperature dropped rapidly to near room temperature, showing good photothermal response reversibility. Among them, the heating rate and peak temperature of BTPG were slightly higher than those of BTG and BTP, indicating that the synergistic effect of TiN and cross-linked network in BTPG achieved more efficient photothermal conversion.

[0074] Figure 6 (b) shows the temperature rise curves of BTPG under different light intensities. As the light intensity increases from one solar irradiance to two solar irradiances, the steady-state temperature of BTPG gradually increases from approximately 85°C to over 120°C, with the heating rate also accelerating. After the lights are turned off, the temperature drops rapidly. This indicates that the photothermal effect of BTPG can be precisely controlled by the light intensity, and it possesses both rapid response and reversibility, providing a flexible and controllable heat source for in-situ viscosity reduction of crude oil under different environmental conditions.

[0075] 7. Oil absorption performance test.

[0076] (1) Crude oil droplet adsorption rate test: A suitable amount of crude oil was dropped onto the BTPG surface, and the time required for the crude oil droplet to be completely adsorbed was observed under one day of sunlight and one day of no light. The results are as follows. Figure 7 As shown in (a), under illumination, crude oil droplets are completely absorbed into the aerogel in just 7 seconds; while under no-light conditions, the adsorption time exceeds 30 seconds. This difference directly demonstrates that the photothermal effect of TiN can heat crude oil in situ, thereby significantly increasing the adsorption rate.

[0077] (2) Oil-water separation effect test: Water was injected into a petri dish and a layer of crude oil was spread on the water surface. BTPG aerogel was placed on the oil film, and the time it took for the crude oil to be completely adsorbed was recorded under light (one sun) conditions. The results are as follows: Figure 7 As shown in (b), under light conditions, it only takes 20 seconds to completely absorb the crude oil on the water surface.

[0078] (3) Saturated adsorption capacity and cycle stability test: BTPG, BTG, and BTP samples were placed in excess crude oil and adsorbed to saturation under one day of sunlight. The mass difference before and after adsorption was measured to calculate the adsorption capacity (g / g). The saturated aerogel was then mechanically squeezed to recover the crude oil, and the adsorption was repeated 10 times. The results are shown below. Figure 8 As shown.

[0079] Figure 8 (a) The bar chart shows that BTPG has a crude oil adsorption capacity as high as 21.49 g / g, which is significantly higher than that of BTP (7.68 g / g) and BTG (9.69 g / g). The ultra-high adsorption capacity of BTPG comes from three synergistic factors: ① The photothermal viscosity-reducing effect of TiN enhances the fluidity of crude oil; ② The three-dimensional porous framework of BC provides ample oil storage space; ③ The GPTMS / PEI crosslinking network improves the structural stability of the framework and prevents collapse after adsorption, which would lead to a decrease in capacity.

[0080] Figure 8 (b) Cyclic testing showed that after 10 oil absorption-extrusion cycles, the adsorption capacity of BTPG remained almost unchanged, consistently at 20.96 g / g (adsorption capacity retention >95%). This result demonstrates that BTPG has excellent reusability, significantly reducing material replacement costs in practical applications.

[0081] 8. Flame retardant performance test.

[0082] (1) Thermogravimetric analysis (TGA): In an air atmosphere, thermogravimetric analysis was performed on pure BC, BPG (BC+GPTMS+PEI crosslinked matrix, without TiN; see Comparative Example 2) and BTPG by heating from room temperature to 800℃ at a heating rate of 10℃ / min. The results are as follows: Figure 9As shown. Figure 9 (a) is the TG curve (vertical axis: mass percentage). Figure 9 (b) is the DTG curve (vertical axis: rate of mass change).

[0083] from Figure 9 (a) It can be seen that pure BC aerogel undergoes rapid thermal decomposition in the approximately 300-400℃ range, with a char residue of only about 17% at 800℃. The decomposition temperature of BPG composite aerogel is slightly earlier, but the char residue increases to approximately 22%. The thermal decomposition process of BTPG composite aerogel is significantly delayed, with a char residue as high as approximately 35% at 800℃. From Figure 9 As shown in the DTG curve in (b), the maximum thermal decomposition rate of BTPG is significantly lower than that of pure BC and BPG. This result indicates that the introduction of TiN and the cross-linking network jointly promote the char formation behavior of the material at high temperatures. The resulting dense carbon layer can effectively suppress heat transfer and the release of combustible gases, significantly improving thermal stability and flame retardant properties.

[0084] (2) Limiting Oxygen Index (LOI) Test: The LOI test was conducted according to GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". The results are as follows: Figure 10 As shown, the LOI of pure BC aerogel is 18.7%, classifying it as a flammable material; the LOI of BPG (i.e., a cross-linked matrix without TiN) is 22.4%, still flammable; and the LOI of BTPG aerogel reaches 24.0%, an increase of 28.3% compared to pure BC. This significant increase in LOI value is attributed to the synergistic physical barrier effect of TiN-induced charring and the cross-linked system, effectively reducing the material's flammability in air.

[0085] (3) Vertical burning test (UL-94 rating): The test was conducted according to Method B (vertical burning method) in GB / T 2408-2021 "Determination of flammability of plastics - Horizontal and Vertical Methods", and the results were determined according to UL 94 criteria. Figure 11 As shown. Figure 11 (a) is pure BC aerogel, which burns rapidly upon contact with a flame; Figure 11 (b) is a BTP composite aerogel, which has a slower combustion rate but still cannot self-extinguish; Figure 11 (c) is a BTPG composite aerogel that self-extinguishes immediately after the fire source is removed, with no molten dripping, achieving the highest rating of V-0. This indicates that the synergistic effect of TiN and the cross-linked network enables the material to rapidly form a dense protective char layer in a fire, blocking oxygen and heat transfer and greatly improving safety.

[0086] 9. Mechanism verification.

[0087] To further verify the oil absorption and flame retardant mechanism of BTPG composite aerogel, the following tests were conducted, and the results are as follows: Figure 12 As shown.

[0088] Figure 12 (a) and (b) are the BET differential pore size distribution curves of BTPG, respectively, where (a) uses linear coordinates and (b) uses logarithmic coordinates. As can be seen from the two figures, the material contains macropores, micropores, and mesopores. This hierarchical pore structure provides ample storage space for crude oil and forms rapid material transport channels, which is the structural basis for achieving high adsorption capacity.

[0089] Figure 12 (c) shows the photothermal temperature rise curves of BTPG under different light intensities. It can be seen that the material can achieve an adjustable temperature rise from approximately 85℃ to over 120℃ within a range of 1-2 solar intensities, with rapid heating response and reversible cooling. This characteristic allows BTPG to flexibly adjust its surface temperature according to ambient light conditions, enabling in-situ heating of the crude oil in contact with it and reducing its viscosity, thus effectively solving the technical problem of the difficulty in rapidly adsorbing high-viscosity crude oil at room temperature.

[0090] Figure 12 (d) Comparison of XRD patterns of BTPG before and after combustion. The characteristic diffraction peaks of TiN (corresponding to PDF#01-071-9845) remain clearly visible after combustion, with essentially unchanged peak shape and position, proving that the TiN crystal structure remains intact during high-temperature combustion. The amorphous carbon formed by the pyrolysis of the BC components intertwines with TiN particles, synergistically constructing a dense physical barrier layer. TiN, as a rigid supporting framework embedded in the carbon layer, effectively prevents the carbon layer from cracking or peeling off at high temperatures, thereby blocking the transfer of oxygen and heat to the unburned internal area, providing the material with excellent flame-retardant properties.

[0091] The above mechanism verification fully demonstrates that the BC / TiN / GPTMS / PEI covalent crosslinking system constructed in this invention achieves the unity of rapid adsorption of high-viscosity crude oil and fire safety of the material through the synergistic effect of hierarchical porous structure, photothermal effect and combustion char formation and stabilization.

[0092] As can be seen from the above examples and performance tests, the BTPG composite aerogel prepared by the present invention has the following excellent effects: (1) Photothermal viscosity reduction and fast oil absorption: Under one sun irradiation, the crude oil droplet adsorption time is only 7 s, the floating oil on the water surface is cleaned within 20 s, and the saturated adsorption capacity reaches 21.49 g / g. (2) Excellent cycle performance: No collapse after 20 cycles under 80% high strain compression, and the adsorption capacity retention rate is >95% after 10 oil absorption-squeezing cycles. (3) High flame retardant safety: LOI reaches more than 24%, UL-94V-0 level, self-extinguishing after leaving the flame, no melting droplets, and the char residue rate at 800℃ is as high as 35%. (4) Clear structure-performance relationship: Characterization data such as FT-IR, XRD, SEM, and BET fully demonstrate the covalent cross-linking network, multi-level porous structure and uniform anchoring of TiN between BC / TiN / GPTMS / PEI, providing solid structural support for various excellent properties.

[0093] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A hydrophobically modified composite aerogel, characterized in that, The surface of the composite aerogel is modified with the hydrophobic modifier trichlorooctadecylsilane to obtain the hydrophobically modified composite aerogel; the water contact angle of the hydrophobically modified composite aerogel is >150°; the composite aerogel before hydrophobic modification comprises: Bacterial cellulose three-dimensional framework; Titanium nitride nanoparticles loaded onto the bacterial cellulose three-dimensional framework; And a covalently cross-linked network formed on the three-dimensional skeleton of bacterial cellulose by γ-glycidoxypropyltrimethoxysilane and polyethyleneimine through an epoxy ring-opening reaction and a silanol condensation reaction; The unmodified composite aerogel has a hierarchical porous structure including macropores, micropores, and mesopores. The titanium nitride nanoparticles are uniformly distributed on the surface and pore walls of the bacterial cellulose three-dimensional framework without aggregation. After 20 cycles of compression at 80% compressive strain, the hydrophobically modified composite aerogel shows no irreversible structural collapse, and the adsorption capacity retention rate is >95% after 10 oil absorption-squeeze cycles. The limiting oxygen index of the hydrophobically modified composite aerogel is 24%, and it achieves a V-0 rating in the UL-94 vertical combustion test. Under one solar intensity irradiation, the hydrophobically modified composite aerogel adsorbs crude oil droplets for only 7 seconds, with a saturated adsorption capacity of 21.49 g / g.

2. A method for preparing the hydrophobically modified composite aerogel according to claim 1, characterized in that, Includes the following steps: (1) The bacterial cellulose dispersion was mixed with titanium nitride nanoparticles and ultrasonically dispersed to obtain a mixed dispersion; (2) Add γ-glycidoxypropyltrimethoxysilane and polyethyleneimine aqueous solution to the mixed dispersion in sequence, stir and react to obtain crosslinking reaction solution; (3) After pre-freezing the cross-linking reaction solution, freeze-dry it to obtain a composite aerogel; (4) The composite aerogel obtained in step (3) is immersed in an organic solvent solution containing trichlorooctadecylsilane, and then dried in a vacuum oven at 60~80℃ for 0.5~2 hours to obtain a hydrophobically modified composite aerogel. In step (1), the amount of bacterial cellulose dispersion is 12.5g, the solid content is 0.80wt%, the amount of titanium nitride nanoparticles is 0.095g, the average particle size is 20nm, and the ultrasonic dispersion time is 10min; in step (2), the amount of γ-glycidyl etheroxypropyltrimethoxysilane is 0.2g, and it is stirred at room temperature for 1h after addition; the amount of polyethyleneimine aqueous solution is 1g, the mass fraction is 20wt%, and it is stirred for 3h after addition; in step (3), the pre-freezing temperature is -80℃ and the time is 2h; the freeze-drying temperature is -55℃, the vacuum degree is ≤10Pa, and the time is 48h.

3. The application of the hydrophobically modified composite aerogel as described in claim 1 in photothermal assisted adsorption of crude oil, characterized in that, Under illumination, the titanium nitride nanoparticles in the hydrophobically modified composite aerogel convert light energy into heat energy to reduce crude oil viscosity, and selectively adsorb crude oil based on the superhydrophobicity of the hydrophobically modified composite aerogel.

4. The application according to claim 3, characterized in that, The hydrophobically modified composite aerogel is used for marine oil spill treatment or oily wastewater purification.

Citation Information

Patent Citations

  • Bio-based aerogel as well as preparation method and application thereof

    CN116874872A

  • Photo-thermal hydrophobic composite aerogel for crude oil adsorption and preparation method thereof

    CN121103331A

  • Bentonite-regulated solar-driven light-heat-electricity conversion composite phase change material as well as preparation method and application of bentonite-regulated solar-driven light-heat-electricity conversion composite phase change material

    CN121574710A

  • Preparation method and application of covalent organic framework and cellulose composite aerogel

    CN122255571A